THE ULTRASTRUCTURAL FEATURES OF THE ADRENAL GLANDS UNDER THE COMBINED EFFECT OF HYPOBARIC HYPOXIA AND STAPHYLOCOCCAL PERITONITIS - Yagubova, S.M. (World of Medicine and Biology, 2021)
The research work is devoted to the study of the pathogenesis and morphogenesis of ultrastructural changes of the adrenal glands under the combined influence of hypobaric hypoxia and staphylococcal infection. Hypoxia and infection develop ultrastructural changes in glandular tissue separately, as well as in combination, which are of a phase nature. In particular, the combined effect of both factors violates the structure of intracellular organelles, reduces their size, leads to deformation and atrophy of adrenocytes, focal growth of connective tissue, and in the course of the experiment, glandular cells adapt to a new environment.
Keywords: hypoxia; staphylococcal infection; adrenal glands; ultrastructure